Food hygiene research: a bibliometric comparison in Iranian and international "Environmental Health" journals - Zahra Aghalari; Hans-Uwe Dahms; Mika Sillanpää (BMC, 2023)
Abstract Background Food hygiene is one of the specialized fields of environmental health, and despite the problems associated with foodborne illnesses, there is no evaluation available that would focus on specialized environmental health journals. The purpose of the present survey is a comparison of the status of food hygiene articles published in Iranian and international journals of environmental health. Methods This cross-sectional descriptive study was performed on all published articles in five Iranian environmental health journals and three international environmental health journals that are among the top 5% and 10% based on SNIP, emphasizing the issue of food. Our data were collected by searching relevant keywords in the articles published during the years (2008-2021), with emphasis on food hygiene. In the checklist, journal and articles information was collected by year of publication, a number of articles, information on authors' participation status in terms of number, gender, organizational affiliation, country and continents, and research centers according to authors' authorship. Statistical analysis of data was performed using descriptive and inferential statistical indices. VOSviewer software was also used to visualize the data. Results In Iranian environmental health journals, out of 2305 articles (7.3%) and out of 6898 articles in international environmental health journals (2.4%) dealt with food hygiene. Food hygiene articles were divided into seven categories, with the largest number of articles on aquatic and agricultural products each with a frequency of 48 articles. Articles related to heavy metals in food were provided by 30.81%. In this study, out of 150 articles, 15 articles were written with the participation of 30 authors from seven continents (Asia, America, and Europe), most of which were from Asia and India. In international environmental health journals, among the main research topics in articles related to food hygiene, the highest number (52.5%) was related to a determination about pollution such as heavy metal concentrations in food. Conclusions Articles published in Iranian and international environmental health journals about food hygiene were limited. According to the increasing prevalence of foodborne illnesses, especially in recent decades, and the importance of paying attention to food hygiene, more targeted studies are needed.